Malaysia Consumer Purchase Intention in Social Commerce: Unravelling the Moderating Impact of Hedonic Motivation - Kumaresan, Kumaran (Universiti Malaysia Sarawak, 2024)
Social Commerce industry involves the use of social media platforms such as Facebook, Tiktok, Instagram, etc. to market and sell products and services. To this, the purpose of this research is to determine the relationship between Theory of Planned Behaviour (TPB) and Technology Acceptance Model (TAM) elements towards consumer purchase intention with the moderating role of hedonic motivation. This hedonic motivation moderates the relationship between the elements of TPB and TAM and consumer purchase intention. The elements that have been included in TPB theory are such as attitude, subjective norm, and perceived behavioural control while elements that have been included in the TAM model are such as perceived ease of use and perceived usefulness. Adopting quantitative methods, data collection was conducted on a sample of 500 respondents that been distributed through survey of online to consumer or people that reached the survey that been shared. For the statistical analysis of this study, software such as SPSS 26.0 and Smart PLS 3.0 were utilized. The findings revealed that five out of ten of the proposed hypotheses were found to be supported for both direct and indirect relationship. The discoveries of the current study contributed to the scholars and practitioners by equipping valuable information supported evidence on the impact of hedonic motivation as moderating in social commerce towards consumer purchase intention.